Assessing language barriers in health facilities in Malawi - Amelia Taylor; Paul Kazembe (BMC Health Services Research)
Abstract Background Language barriers in healthcare lead to miscommunication between professionals and patients, thereby reducing the quality of and equitable access to healthcare. In African countries, the recognition and formal study of these barriers is severely limited despite Africa having more languages than any other continent. Our study investigates language barriers in healthcare facilities in Zomba district in Malawi, where three major local languages are spoken. Methods We employed a mixed methods approach and conducted a questionnaire-led study. Data were gathered at 22 health facilities, from 79 healthcare professionals and 312 outpatients using a semi-structured questionnaire. Findings were corroborated using document analysis to review legislation and policies, curriculum documents and patient notes. Results Language discordance emerged as a problem for professionals and patients. Both faced challenges due to vocabulary limitations for medical terms in English and Chichewa. Professionals did not receive training on how to effectively communicate medical concepts in local languages. Most patients did not speak English, which was used for all written records. Patient understanding of the information given to them verbally during consultations or in written health notes was very low, and this diminished their confidence in the diagnosis or treatment they received. Social factors including gender, age or patient experience, as well as patient literacy or perceived low literacy, poor rapport between healthcare professionals and patients, and a lack of privacy during consultations all exacerbated communication issues. Consequences of language barriers included unsatisfactory care experiences and compromised exchanges of health information. Strategies used by professionals to cope with these challenges were flexibility in the choice of language, reliance on physical checks and non-verbal communication indicators and the occasional use of ad-hoc interpretations. Conclusion Language barriers in healthcare facilities in Malawi have serious implications on the quality of healthcare provided. We propose solutions such as the development of dictionaries with phrases for symptoms and conditions, sensitisation courses that incorporate language considerations for both professionals and patients. Policies such as the provision of interpreters and staff allocation are discussed. We recognise that coordinated efforts at national and international levels are key to securing significant funding for effective interventions.